Website E-Commerce sebagai Media Promosi Penjualan Pengolahan Hasil Laut Kelompok Istri-Istri Nelayan di Karangantu - Novi Sofia Fitriasari; Ayang Armelita Rosalia; Luthfi Anzani; Della Ayu Lestari; Kukuh Widiyanto; Wildan Aprizal Arifin; Denta Tirtana; Fawaz Fawaz; Cakra Rahardjo (Universitas Mathla'ul Anwar Banten, 2020)
E-COMMERCE WEBSITE AS A MEDIA FOR PROMOTING SALES OF FISHERMEN'S WIFE GROUP SEAFOOD PROCESSING IN KARANGANTU. Currently fish caught from husbands who work as fishermen can only be marketed fresh, and if they are not sold, they will be discarded or used as animal feed. Fish product development processing is being carried out by agencies for groups of fishermen's wives. We carried out community service by marketing team that can help increase fishermen household income. Marketing strategy is by creating a website. The objectives of community service through this activity are as follows: (a) Introducing fishermen's wives to information media for sales, (b) Creating Banten Bahari E-Commerce Website (BAHARI) which later can be used as marketing media by fisherman wives. Method to achieve the first goal is by community education, and for online we use the Waterfall method. The socialization of online media introduction for marketing marine products in Karangantu was well responded by fishermen's wives. Making the BAHARI website is one of promotional media that fishermen's wives can use in the future.